Evaluating Sorghum bicolor resistance to Solidago canadensis invasion under different nitrogen scenarios - Anas, Muhammad; Khan, Irfan Ullah; Alomrani, Sarah Owdah; Nawaz, Mohsin; Huang, Zhi-Yun; Alshehri, Mohammed Ali; Al-Ghanim, Khalid A.; Qi, Shan-Shan; Li, Jian; Dai, Zhi-Cong; Ali, Shafaqat; Du, Dao-Lin (Frontiers in Plant Science, 2024)
Ecosystem exposure to the biological invasion such as plant invasion could contribute to extinction of native species, loss of productivity and ecosystem balance. Solidago canadensis (S. canadensis) is a highly invasive species forming monocultures in China, Europe, Asia, Australia, and New Zealand. It was designated as a notorious invasive species by the Chinese government. It adversely affected the agro-ecosystem's ability to germinate various plant seeds, including wheat, lettuce, and pepper, which could lead to food insecurity. This study was conducted to control invasive species S. canadensis by utilising competitive Sorghum bicolor (S. bicolor) as a cover plant. Sorghum bicolor exudes allelochemicals like sorgoleone from its root which supress the activity of photosystem II of nearby plants. The synthesis of sorgoleone depends on supplies of nitrogen. The present study involved the cultivation of S. bicolor alongside the invasive species S. canadensis, with three different invasion levels (high, medium, and low) and three different nitrogen forms (ammonical, nitrate, and combined ammonical and nitrate nitrogen) applied as a modified Hogland solution. Sorghum bicolor expressed higher performance over the invasive species under ammonical and combined nitrogen forms under low and medium invasion levels. While, even at greater levels of invasion, S. bicolor was unable to be suppressed by S. canadensis. However, the plant height and dry biomass of S. bicolor was significantly high across both nitrogen forms. Leaf area, CO2 uptake and activity of photosystem II of S. canadensis were unable to sustain its growth under low invasion. Plant biomass of S. canadensis was suppressed upto 80% and the relative dominance index of S. bicolor was 5.22 over S. canadensis. There was a strong correlation was between CO2 uptake, leaf area and plant biomass. Principal component analysis showed that the first four components had a total variance of 96.89%, with principal component 1 (PC1) having the highest eigen value at 18.65. These promising findings suggested that S. bicolor, whose high intensity might be employed to control the invasion process for environmental safety, might be able to recover the barren ground that S. canadensis had invaded.